THE EFFECT OF HOSPITAL REPUTATION AND QUALITY OF SERVICE ON PATIENT SATISFACTION (CIMAHI PRIVATE HOSPITAL) - Wala Erpurini (Jurnal Scientia, 2022)
This study was conducted on patients of Mitra Kasih Cimahi Hospital. The purpose of this study was to determine the influence of hospital reputation and service quality on patient satisfaction in Cimahi private hospital. The research method that will be used in this study is Survey Research. In this study the unit of analysis is the individual patient Cimahi Private Hospital. The sample in this study as many as 75 respondents. Sampling random sampling method is a sampling technique used in this study. The method of analysis using multiple linear regression analysis, in addition to testing the validity and reliability of research instruments. Based on the results showed that there is no direct relationship between the reputation of the hospital (X1) with patient satisfaction (Y). second, there is a relationship between the quality of Service (X2) with patient satisfaction (Y). Third, there is a simultaneous influence between the reputation of the hospital (X1) and quality of Service (X2) with patient satisfaction (Y).